Conformational Analysis of Peptides and Glycopeptides Derived from the Consensus Sequence for β-O-Glucosylation - J. Somovilla, Victor; Martinez-Saez, Nuria; Fernandez-Tejada, Alberto; G. de la Torre, Beatriz; Andreu, David; Jimenez-Barbero, Jesus; L. Asensio, Juan; Avenoza, Alberto; H. Busto, Jesus; Corzana, Francisco; M. Peregrina, Jesus (Current Topics in Medicinal Chemistry, 2014)
Cys-Xxx-Ser-Xxx-Pro-Cys (Xxx= any amino acid but Pro) is the most common sequence present in naturally occurring peptides and proteins glycosylated with β-O-glucose (β-O-Glc). Taking into account the lack of studies concerning the spatial disposition of this sequence, we have synthesized and analyzed, in aqueous solution, the conformational behavior of peptides and a glycopeptide derived from the particular fragment Cys-Ala-Ser-Ser-Pro-Cys. This sequence is found in the crystal structure of the complex of blood coagulation factor VIIa with soluble tissue factor. Our studies, based on the use of NOESY experiments in combination with molecular dynamics (MD) simulations, indicate that for this particular fragment, initially characterized by a type I β-turn motif, the glycosylation with β-O-Glc forces the peptide backbone into an extended conformation. This conformation is stabilized by the presence of both hydrogen bonds and water pockets between the peptide and the sugar moieties.
Keywords: Conformational analysis